(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
ينشد هذا البحث تقديم صورة واضحة نوعاً ما عن الذات المتفردة المقدمة على الجهاد عند الشعراء الفاتحين، إذ كثيراً ما كان الشاعر الفاتـح يتناول ذاته المتفردة في الجهاد، فيذكر بلاءه الحسن في قتال العدو، وبطولاته النادرة واقتحامه الوغى، غير مكترث بالجموع الغفيرة لجيش الأعداء، وكنا نرى في العصر الجاهلي انضواء الشاعر تحت لواء القبيلة، أما الآن، فالأمر مختلف، إذ اكتسى هذا الفخر الفردي حلة الانضواء القلبي الطوعي تحت راية الإسلام الواحدة. وهذه الدراسة ستكون تحليلية لا تعتمد منهجاً معيناً، بل تستعين بكل المناهج الدراسية الأدبية، تجنباً للتقصير المحتمل الكامن في أحادية المنهج، ورغبة في الحصول على نوع قريب من التكامل الدراسي الذي يقدم لنا صورة واضحة عن الموضوع المتناول. This study tries to present a somewhat clear description of the distinguished self of the Islamic conquering poet who, very often, described his distinguished self in fighting the enemy without being afraid of death or the army large number. The poet, before Islam, used to fight for his tribe. After Islam, things changed. Now the poet is voluntarily fighting for only the one Islamic flag. This study is analytical and does not adopt a specific method, but depends on all literal study methods. This is to avoid any possible shortage that often results from method restriction, and to achieve an almost perfect picture of the study subject.